Skema JCM (Joint Crediting Mechanism) pada Investasi Fasilitas Pemurnian Biogas di Pabrik Kelapa Sawit - Febijanto, Irhan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Until now, the use of biogas in Palm Oil Mill (POM) is still limited to use as a fuel for Biogas Power Plant or utilize an additional boiler fuel. The use of biogas to be taken to other places is constrained by the remote location of POM and the transportation method. However, by converting biogas into bio-CNG, it can be used as vehicle fuel. The investment feasibility study of bio-CNG production facilities was carried out for two case studies, in POM with a capacity of 30 t/hr and 60 t/hr. The funding uses 100% of the equity fund and subsidy of the Joint Crediting Mechanism (JCM) scheme. Using the JCM scheme, the value of investment gets 50% funding assistance, and carbon credits from the reduction of Greenhouse Gas (GHG) emissions belong to the Japanese government. As a result of the study, it is known that the development of bio-CNG production facilities with 100% equity, IRR of both POM is below 11.08%, so it is not economically feasible. From the sensitivity analysis, it indicates that the increase in selling price of bio-CNG of +10%, a decrease in the investment of -10%, an increase in biogas input of +10% still cannot increase the Internal Rate of Return (IRR) value. Funding from JCM of 50% of the investment value increased the IRR value of 30t/hr and 60t/hr increasing from 6.54% to 18,29% and from 8.13% to 20.82%, respectively. The values of IRR became higher rather than the benchmark (IRR=11.08%). Carbon emissions reduction of the operation of the bio-CNG production facility and the use of bio-CNG for vehicle fuels in both of POMs are 38,735 tCO2/yr and 77,471 tCO2/yr, respectively. Using subsidy from carbon credits or other incentives will significantly help improve the economically feasible of bio-CNG production facilities in POM.